Pemerkasaan Konstruk Amalan Pendidikan Berimpak Tinggi Berteraskan Dasar Pendidikan Rabbani Kelantan: The Empowerment of High-Impact Educational Practice Construct Based on Kelantan Rabbani Education Policy - Rahim Kamarul Zaman; Mujiburrahman Muhammad Saleh; Nur Shahidah Ab Hamid; Mazlan Ibrahim; Azizi Umar (RABBANICA - Journal of Revealed Knowledge, 2024)
The transformation of Malaysia’s higher education system in the 21st century has seen substantial progress. The Malaysian Education Development Plan for Higher Education (2015-2025) prioritises a holistic, comprehensive and integrated approach to curriculum development. The plan is also supported by High-Impact Educational Practices (HIEP) to produce holistic graduates who are knowledgeable and ethically aligned with the National Higher Education Philosophy. However, the holistic element appears very subjective, making it difficult for Higher Education Providers (HEPs) to develop an integrated curriculum based on these aspirations. ‎This study aims to analyse how the Kelantan Rabbani Education Policy (DPRK), introduced by the Kelantan State Government in 2018, can support the aspirations of HIEP. Using thematic content analysis, this qualitative study examines the correlation between the 9 DPRK principles, the four core features of HIEP, and Leap 1 of the Malaysian Education Development Plan 2015-2025 (Higher Education). The study’s results reveal the significant potential of integrating DPRK into the implementation of ‎HIEP. The impressive 78.1% potential integration of all nine principles to enhance the four construct characteristics of HIEP underscores its importance. Specifically, 36 out of 46 best practices were identified as suitable for integration into HIEP aspirations, highlighting the promising prospects of this approach. In conclusion, this study found that DPRK deserves to be dignified as a HIEP quality empowerment module and officially practised in national and global higher education systems. ‎ Transformasi sistem pendidikan tinggi di Malaysia dalam abad ke-21 telah mencatatkan kemajuan yang ketara. Berdasarkan Pelan Pembangunan Pendidikan Malaysia 2015-2025 (Pendidikan Tinggi), aspek pembangunan kurikulum yang holistik, bersepadu dan konstruktif telah digariskan sebagai lonjakan utama. Pelan berkenaan turut disokong Amalan Pendidikan Berimpak Tinggi atau High-Impact Educational Practices (HIEP) bagi menghasilkan graduan holistik yang berilmu dan berakhlak sejajar dengan Falsafah Pendidikan Tinggi Kebangsaan. Namun, elemen holistik berkenaan kelihatan sangat subjektif dan menyukarkan Pemberi Pendidikan Tinggi (PPT) membangunkan kurikulum bersepadu berpandukan aspirasi berkenaan. Justeru, kajian ini dikemukakan bagi membincangkan potensi pemerkasaan aspirasi HIEP melalui pengaplikasian Dasar Pendidikan Rabbani Kelantan yang telah digagaskan oleh Kerajaan Negeri Kelantan pada tahun 2018. Dengan mengaplikasi metode analisis kandungan secara tematik, kajian berbentuk kualitatif ini meneliti tahap keselarian aspirasi 9 prinsip DPRK, 4 ciri teras HIEP dan Lonjakan 1 Pelan Pembangunan Pendidikan Malaysia 2015-2025 (Pendidikan Tinggi). Hasil kajian mendapati, potensi pengintegrasian DPRK dalam konstruk HIEP adalah amat signifikan. Konstruk 9 prinsip DPRK yang menggariskan 46 amalan terbaik didapati sesuai disepadukan dalam aspirasi HIEP. Kesimpulannya, kajian ini mendapati DPRK wajar dimartabatkan sebagai modul pemerkasaan kualiti HIEP dan dipraktikkan secara rasmi dalam sistem pendidikan tinggi peringkat nasional dan global.